Analisis Tingkat Kecakapan Hidup dalam Perspektif Dimensi Pengambilan Keputusan Berdasarkan Gender di Klub Bulutangkis kota Bandung - Naufal D, Kevin; Subroto, Toto; Hambali, Burhan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to analyze the level of life skills in the decision-making dimension owned by badminton athletes in the West Java using descriptive methods. Total of 50 athletes consisting of 29 male athletes and 21 female athletes participated in this study. The research instrument is in the form of a life skills scale of sport (LSSS) developed by Cronin which aims to measure the level of life skills in the decision-making dimension of badminton athletes. Data was obtained using descriptive statistical analysis and independent sample T-test using SPSS software version 29.0. The results showed that the level of life skills in the decision-making dimension of male badminton athletes was the same as female athletes. Both are in the medium-level category with a percentage of 72%. Based on gender, male athletes are in the medium category with a percentage of 34% and female athletes in the medium category also with a percentage of 38%. while in the independent sample analysis, the T-test obtained a sig value. (2-tailed) = 0.047/0.407. In conclusion, there is a significant difference between the level of life skills in the decision-making dimension of male athletes and female athletes. Key words: Badminton, Decision-making, Life skills,